2015
DOI: 10.5267/j.ijiec.2015.6.002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization of process parameters using Taguchi method and grey relational analysis during turning AA 7075/SiC composite in dry and spray cooling environments

Abstract: Turning experiments were carried out on AA 7075/SiC composite workpiece in dry and spray cooling environments based on L16 Taguchi design of experiments. Multiple performance optimization of process parameters was performed using grey relational analysis. The performance characteristics considered were average surface roughness, cutting tool temperature and material removal rate. Uncoated carbide inserts were used for machining the workpiece in a high speed precision lathe. A grey relational grade obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…However, if the response is "larger is better", then Eq. (7) is used for its normalization (Tzeng et al, 2009;Mishra et al, 2015).…”
Section: Optimization For Multiple Performance Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the response is "larger is better", then Eq. (7) is used for its normalization (Tzeng et al, 2009;Mishra et al, 2015).…”
Section: Optimization For Multiple Performance Characteristicsmentioning
confidence: 99%
“…High specific stiffness and strength, better high temperature properties and thermal capacity; and low thermal expansion coefficient make the Al-based MMCs suitable for application in aerospace, marine, automotive drive shaft fins, explosion engine components, heat sinks, solar panels and antenna reflectors etc. (Alaneme & Aluko 2012;Das et al, 2014;Das et al, 2015;Mishra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al [19], during straight turning the SiC p impregnated aluminium 7075 MMCs by uncoated WC tools in both dry and spray cooled conditions, noticed lower values of surface roughness and tool temperature in spray cooled condition than those in dry condition for the identical levels of speed, feed and cutting depth. Bhuyan and Routara [3] optimized the machining parameters through VIKOR followed by entropy weight method while electro discharge machining (EDM) Al/18 wt.% SiC p MMCs, and reported that 116 µsec pulse on time, 20 Amp pulse current and 0.836 Kg/cm 2 flushing pressure were the optimized cutting factors for the multi performance machining criteria (rate of material removal, rate of tool wear, radial overcut and average roughness of machined surfaces).…”
Section: Introductionmentioning
confidence: 98%
“…Aluminium matrix composites (AMCs) impregnated with hard ceramic particulates are replacing the conventional materials in automobile, aerospace, marine and military applications for their significant properties; like high temperature resistance, high stiffness and high strength to weight ratio (Manna & Bhattacharyya, 2003;Yingfei et al, 2010;Mishra et al, 2015;. Existence of hard SiC particulates in the composites causes difficulty in machining with carbide tip tools, leading to inferior surface quality and too much tool wear (Manna & Bhattacharyya, 2003;Panda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%